Current situation and compliance with regulations on hazardous waste in mechanical workshops in Progreso neighborhood, Acapulco, Guerrero, Mexico - Juárez Agis, Alejandro; García Sánchez, Silberio; Maldonado Astudillo, Rayma Ireri; Olivier Salome, Branly; Zeferino Torres, Jacqueline; Torres Espino, Gloria; Rivas Gonzalez, Mayra (Acta Universitaria, 2023)
Hazardous waste is generated by industrial activities and represents sources of pollution. The purpose of this investigation was to carry out a diagnosis of the handling, storage, and final disposal of the hazardous waste generated in 64 mechanical workshops in Acapulco, Guerrero, Mexico. A semi-structured questionnaire was applied to 64 people, with a non-probability sampling for convenience. As a result, it was observed that the workshops generate hazardous waste in the following quantities: used oil 27.98 kg/month; empty containers of oil, brake fluid, and antifreeze 25.43 kg/month; used oil filter 5.59 kg/month; solvent 5.50 kg/month; aerosol containers and paint containers 3.71 kg/ month; paint, solvent, and resin residues 3.10 kg/month; tow, cloth, and cardboard impregnated with oil 2.46 kg/month; residual fat 2 kg/month; batteries 1.86 kg/month. Respondents state that they are aware of the legislation; however, 45% of workshops deposit solid and hazardous waste as if they were for domestic use.